Analysis of Molecular Biomarkers in Resected Early-Stage Non-Small Cells Lung Cancer: A Narrative Review - Filippo Tommaso Gallina (Cancers, 2022)
Next-generation sequencing has become a cornerstone in clinical oncology practice and is recommended for the appropriate use of tailored therapies in NSCLC. While NGS has already been standardised in advanced-stage NSCLC, its use is still uncommon in the early stages. The recent approval of Osimertinib for resected EGFR-mutated NSCLC in an adjuvant setting has launched the hypothesis that other targeted therapies used in metastatic patients can also lead to improved early-stage outcomes of NSCLC. The impact of molecular biomarkers on the prognosis of patients undergoing radical surgery for NSCLC is still unclear. Notably, the heterogeneous populations included in the studies that analysed surgical patients could be the main reason for these results. In this review, we report the most important studies that analysed the impact of principal molecular biomarkers on the survival outcomes of patients who underwent radical surgery for NSCLC.